Volitional effort formation in senior preschool children with speech impairments using visual modeling - Piskun, Olga; Shilova, Olga
The aim of this research is to investigate the process of volitional effort formation in senior preschool children with general speech underdevelopment (GSU) by visual modelling. The study was conducted using theoretical and practical methods and methods of mathematical statistics. The main indicators of volitional effort formation were determined at the ascertaining stage using methods developed by Smirnova. Methods were partially adapted for 5-year-old children with GSU, and a map of observations was made. Based on the results of observations of children in experimental and control groups (a total of 38 children), pupils were allocated into four categories according to their behavior in direct educational activities. At the control stage of the study, (after the special work on volitional effort formation by visual modeling) children in the experimental group demonstrated positive dynamics in volitional regulation. The number of children, achieved a high level in volitional effort formation, has increased, and the number of children with a lower average level has decreased, moreover, none of the pupils remained at a low level. The results of the study showed the effectiveness of the work on volitional effort formation using the method of visual modeling.
Keywords: Speech impairments